Aggressive central giant cell granuloma: A rare case report - Sunanda Chavva; Canchi Dhawalraj; Raj K Badam; Nallan CSK Chaitanya (Wolters Kluwer Medknow Publications, 2017)
Giant cell granuloma is a benign proliferative pathological lesion of the bone accounting for less than 7% of lesions of the jaw, predominant in females and most commonly seen in anterior segment of jaws. Mandible is more commonly affected. Radiographically, the lesion may present with diffuse or irregular borders, sometimes leading to expansion of cortex, displacement of teeth, or root resorption. We present a case of aggressive central giant cell granuloma in a 45-year-old female patient in the right mandibular alveolar ridge presenting as an irregular mass causing displacement of teeth.